Boosted up stability and activity of oxygen vacancy enriched RuO2/MoO3 mixed oxide composite for oxygen evolution reaction. (10th July 2020) - Tariq, Muhammad; Wu, Yiyi; Ma, Chenglong; Ali, Meesam; Zaman, Waqas Qamar; Abbas, Zain; Ayub, Khurram Shahzad; Zhou, Jiacheng; Wang, Gehui; Cao, Li-mei; Yang, Ji
Abstract: Iridium free, acidic-stable, cost-effective, and efficient oxygen evolution reaction (OER) electrocatalyst is considered to be the bottleneck in the quest for sustainable energy production/storage devices. RuO2 has been proved as a highly active and standard OER electrocatalyst with poor stability. Herein, we are successfully providing the facile approach to synthesize the mixed oxide composite of RuO2 tailored with MoO3 . Fifty percent reduction of noble metal contents, two times enhanced activity and excellent durability as compared to pure homemade and commercial RuO2 have been confirmed by numerous characterization techniques. Enhanced electrochemical performance of best mixed oxide composite is observed due to increasing number of oxygen vacancies, electronic distortion, lower oxidation state of noble metal, and reduced value of the Tafel slope. Furthermore, the best composite shows the 7-fold increase in electrochemical surface area, 3.2 times improvement in the bulk mass activity, and less value of overpotential. Graphical abstract: Image 1 Highlights: Facile synthesis of RuO2 particles decorated on MoO3 for oxygen evolution reaction. Mixed oxide containing 50% noble metal robustly performs in corrosive environment. Electronic distortion, lower oxidation state and increase of oxygen vacancies. Improvement of numerous electrochemical characteristics of mixed oxide composite.